Akuntasi Keuangan pada Dana Desa di Desa Grinting Brebes - Roni Roni (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to conduct an in-depth analysis of the implementation of financial accounting principles for village funds in the management of funds in Grinting Village, Bulakamba District, Brebes Regency. The research focuses on all stages of village fund management, including planning, implementation, administration, reporting, and accountability, which are essential elements of sound financial governance. A descriptive qualitative approach was employed to provide a comprehensive understanding of the observed phenomenon. Data were collected through in-depth interviews with village officials, direct observations of the fund management process, and document analysis, encompassing both primary and secondary data. The findings reveal that the application of financial accounting principles for village funds in Grinting Village generally complies with the provisions stipulated in the Minister of Home Affairs Regulation (Permendagri) Number 113 of 2014 concerning Village Financial Management. Furthermore, the principles of transparency, accountability, participation, orderliness, and budget discipline were applied in managing the 2024 fiscal year village funds. However, the study also identified several challenges, such as limited human resources with adequate accounting knowledge and the suboptimal use of technology in the reporting process. These constraints may affect the effectiveness and efficiency of village fund management. Therefore, improvement efforts are necessary, including capacity building for village officials, continuous training, and the utilization of information technology to support more transparent, accountable, and regulation-compliant financial management practices.